Persepsi Mahasiswa Agribisnis terhadap Citra Profesi Petani - riska_amelia karis; Reny Sukmawani; Neneng Kartika Rini (Ma'soem University, 2026)
This study aims to analyze Agribusiness students' perceptions of the image of the farming profession, focusing on students from the Agribusiness Study Program at the Faculty of Agriculture, Muhammadiyah University of Sukabumi. The method used is descriptive with a Likert scale. Primary data was obtained through a questionnaire from 65 respondents selected using a simple random sampling technique. Analysis was carried out by calculating scores and percentage indices to determine the level of respondents' assessment of the image of the farming profession. The results showed that the image of the farming profession is in the good category with an index value of 71.09%. Students have a positive view of the prospects of the agricultural sector in the future, but there are still negative views related to social status, income, and modernization. This indicates a gap between views and career interests in the agricultural sector. Therefore, efforts are needed to improve the image of the farming profession through modernization, improving welfare, and the role of education and media in building a positive image of the farming profession.